MANAJEMEN YAYASAN BUDI MULYA PALANGKA RAYA PADA LEMBAGA PENDIDIKAN - Azhary, M.; Ahmadi, Ahmadi; Hikmah, Nurul (STKIP Pesisir Selatan, 2026)
This study aims to analyze the planning, implementation, and supervision of educational management at the Budi Mulya Foundation. This research employs a qualitative approach using a case study design. The research subjects consist of the head of the foundation, the head of the madrasah, and the vice head of the madrasah for curriculum affairs. Data were collected through interviews, observations, and documentation studies. Data validity was ensured through source triangulation and technique triangulation. The results indicate that planning of educational institutions at the Budi Mulya Foundation in Palangka Raya is carried out through regular coordination meetings involving the foundation, school principals, and teachers to design key activities such as teaching and learning processes, new student admissions, and school examinations. The implementation of educational institutions is conducted based on an annual work plan with a clear division of responsibilities between the foundation and the educational institutions, as well as integration of academic and non-academic activities. Meanwhile, supervision of educational institutions is conducted through evaluation meetings integrated with academic activities, such as examinations, grade promotion, and graduation.